Battlefields and marketplaces - Halvor Mehlum; Karl Ove Moene (University of Oslo, Department of Economics, 2002)
Divided societies in the developing world experience wasteful struggles for power. We study the relationship between political stability and resources wasted in the struggle within a model of competitive power contests. The model of power contests is similar in structure to models describing oligopolistic market competition. This analogy helps us in deriving results that are new to the conflict literature. We show, for example, that the Herfindahl-Hirschman index can be interpreted as a measure of power concentration and that a peace treaty between Þghting groups have a parallel in tacit collusion between firms in a market.
Keywords: C70; D23; D74; 330; Violent conflicts; Rent-seeking games; Herfindahl-Hirschman index; Oligopolistic competition; Rent Seeking; Konzentrationsindex; Spieltheorie; Politischer Konflikt